Neurologists should endorse active transportation for their patients. Issue 4 (August 2017) - Foster, Daniel
Abstract : Abstract: It has been well-established that social determinants prevent far more deaths than medical care. Both behavior and social circumstance are closely linked to transportation. The connection between health and transportation is both direct (pedestrian injury, for example) and indirect (commuting access to work leading to employer-based health insurance, for example). Thus, transportation policy and health policy are interrelated. Neurologists should join community partnerships to promote safe and healthy transportation options for all people but especially for their patients.